2017
DOI: 10.1111/pce.13033
|View full text |Cite
|
Sign up to set email alerts
|

Shining a light on the Arabidopsis circadian clock

Abstract: The circadian clock provides essential timing information to ensure optimal growth to prevailing external environmental conditions. A major time-setting mechanism (zeitgeber) in clock synchronization is light. Differing light wavelengths, intensities, and photoperiodic duration are processed for the clock-setting mechanism. Many studies on light-input pathways to the clock have focused on Arabidopsis thaliana. Photoreceptors are specific chromic proteins that detect light signals and transmit this information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 192 publications
(353 reference statements)
5
96
0
Order By: Relevance
“…OsPRR37 in regulating gene transcription and the response to light or other stimuli. These findings are consistent with OsPRR37 as both a transcriptional repressor and a clock gene that is regulated by light and other stimuli (Dubois, Claeys, Van den Broeck, & Inze, 2017;Farré & Kay, 2007;Haydon, Mielczarek, Robertson, Hubbard, & Webb, 2013;Murphy et al, 2011;Oakenfull & Davis, 2017). However, we found that the enriched GO categories in the up-regulated rhythmic DEGs were the protein amino acid phosphorylation, protein modification process, phosphate metabolic process, signal transducer activity and protein kinase activity, etc.…”
Section: Osprr37 Represses the Expression Levels And Amplitudes Of supporting
confidence: 86%
“…OsPRR37 in regulating gene transcription and the response to light or other stimuli. These findings are consistent with OsPRR37 as both a transcriptional repressor and a clock gene that is regulated by light and other stimuli (Dubois, Claeys, Van den Broeck, & Inze, 2017;Farré & Kay, 2007;Haydon, Mielczarek, Robertson, Hubbard, & Webb, 2013;Murphy et al, 2011;Oakenfull & Davis, 2017). However, we found that the enriched GO categories in the up-regulated rhythmic DEGs were the protein amino acid phosphorylation, protein modification process, phosphate metabolic process, signal transducer activity and protein kinase activity, etc.…”
Section: Osprr37 Represses the Expression Levels And Amplitudes Of supporting
confidence: 86%
“…, 1995b; Somers et al . ; Oakenfull & Davis ). An essential function of the clock is to direct downstream processes to take place at the optimal time of day.…”
Section: Entrainment Of the Clockmentioning
confidence: 99%
“…The expression of dawn‐phased clock components tends to be induced by light, whereas the Evening Complex has been identified as a likely hub for signal integration as it interacts directly with the photo‐ and thermo‐sensor phytochromeB (phyB; Hsu & Harmer, ; H. Huang et al ., ; Ezer et al ., ). The role of phytochrome, cryptochrome and UVR8 photoreceptors in the circadian system has recently been discussed elsewhere (Oakenfull & Davis, ). Instead, this review focuses on our understanding of how metabolic changes induced by environmental fluctuations affect circadian timing.…”
Section: The Circadian System Is Responsive To Environmental Changementioning
confidence: 99%
“…Huang et al, 2016;Ezer et al, 2017). The role of phytochrome, cryptochrome and UVR8 photoreceptors in the circadian system has recently been discussed elsewhere (Oakenfull & Davis, 2017). Instead, this review focuses on our understanding of how metabolic changes induced by environmental fluctuations affect circadian timing.…”
Section: The Circadian System Is Responsive To Environmental Changementioning
confidence: 99%